Design of Robust & Predictive Controller for Altitude Stabilization and Trajectory Tracking of a Quad-Copter - Bushra, S.; H.Memon, H.; Nighat, A.; S.Chowdhry, B. (International Journal of Engineering and Technology, 2018)
Controlling the non-linear dynamics of the quad-copter has stimulated many control engineers to investigate & design the variety of controllers in order to control and stabilize the various aspects of quad copter such as the attitude, altitude, heading, xy position and even in trajectory following in the presence of disturbance. This is because of the quad-copter’s application and importance in the variety of fields such as military, rescue, agriculture, surveillance, investigation, etc. Altitude control & stabilization problem of the quad-copter is the main focus of this research study. A dynamic and predictive controller is designed for the said problem based on Model predictive controller. In order to deal with the uncertainties & dynamics of the model during the flight operation and to ensure the robustness for the designed system, the sliding mode control technique is presented. Proportional-Integral-Derivative controller is also implemented for the system to make a comparative analysis with the rest of the designed controllers. Apart from controlling & stabilizing the altitude, these controllers are also capable for the trajectory tracking of the quad-copter. The six degree of freedom coupled model of quad-copter is taken into account and the same is then de-coupled for quad-copter hovering. In order to confirm the asymptotically stable state of the system, stability analysis of the proposed controller design is also done. The designed system is simulated in MATLAB/SIMULINK and also the comparison for robust and predictive controller is presented in order to depict the degree of potency of the proposed controller.